CISSAMPELOS PAREIRA: PROTEIN-LIGAND DOCKING TO IDENTIFY SUITABLE TARGETS FOR HEPATOCELLULAR CARCINOMA (HCC) BY IN-SILICO TECHNIQUES AND TOOLS (Jurnal Teknologi (Sciences & Engineering), 2015)
Protein-ligand interaction plays a major role in identification of the possible mechanism by which a ligand can bind with the target and exerts the pharmacological action. The present study aims to identify new possible candidates for treating Hepatocellular Carcinoma (HCC) by docking the reported phytochemicals present in Cissampelos pareira with the well known HCC targets using in-silico techniques. Although C. pareira demonstrated in vitro and in vivo anti-heptatocellular carcinoma activities, the mechanism remains uncertain. Selected compounds from C. pareira were docked using GLIDE software with known targets of hepatocellular carcinoma viz. Aurora Kinase, c-Kit, Fibroblast Growth Factor (FGF), Nuclear Factor kappa B (NF-kB), B-cell lymphoma-extra large (Bcl-xL) and Vascular Endothelial Growth Factor (VEGF). Among the compounds docked, pareitropone and pareirubrine B exhibited good hydrogen bonding interactions and binding energy with the targets of HCC taken in the study. Hence these compounds deserve consideration for further studies towards HCC.
Keywords: Cissampelos pareira; GLIDE; docking